Structure design on improving injection performance for venturi scrubber working in self-priming mode. (April 2015) - Zhou, Yanmin; Sun, Zhongning; Gu, Haifeng; Miao, Zhuang
Abstract: The venturi scrubber working in self-priming mode is one of the most efficient gas cleaning devices to remove the radioactive particles and gases from gaseous stream during severe accident in nuclear power plant. This paper focus on improving injection performance in a split type self-priming venturi scrubber, the static pressure distributions at gas and liquid channels in the scrubber are studied emphatically, the experimental results indicate that pressure at the center of nozzle exit is lower than at the wall, and the variation laws in radial are different with increasing gas velocity. When the average gas velocity at throat U avg = 64.3 m/s, the static pressure difference between center and wall is 2.1 KPa; with the increase of gas velocity, pressure at centre and wall reduce gradually and the pressure difference become significantly, when the average gas velocity U avg = 225.8 m/s, pressure at the center is lower 23.2 KPa than at the wall, relative deviation is about 45.6%. However, when U avg ≥ 230 m/s, the static pressure is not continue to decrease but reverse to recover with increasing gas velocity, and recovery rate at the wall is greater than at the center. The condition before the transition point (Uavg < 230 m/s) is defined as velocity dominate area, in this area, pressure will always decrease with increasing gas velocity; the condition after the point ( U avg ≥ 230 m/s) is defined as resistance dominate area, while pressure in this area will reverse to recover, the venturi scrubber design should be ensured in velocity dominate area. The injection performance of self-priming venturi scrubber is closely relate to pressure distribution characteristics at nozzle exit, in condition of no injection or injecting air, pressure at liquid channel is consistent with the pressure at the wall of nozzle exit, which is higher than the average static pressure; when injecting water, an additional pressure increment will generate at liquid channel duo to the momentum exchange between gas and liquid, and lead to the effective pressure difference for injection reduce further. On this occasion, the influence of liquid channel area and resistance coefficient on injection performance become important, increase liquid channel area is effective for improving injection flow rate. Highlights: Static pressure distributions at nozzle exit are studied under different gas velocity. Static pressure distributions at liquid channel cross section are studied under no injection and injection conditions. The influence of static pressure distributions on injection performance is investigated. Feasible structure design to further improve injection flow rate is proposed.